Palladium catalyzed reactions on glycal scaffolds : syntheses of glycal derivatives and C-glycosides - Bai, Yaguang (2015)
Glycals are a group of carbohydrate derivatives which were first synthesized more than a century ago. The reactive carbon-carbon double bond between C1 and C2 has stimulated a huge number of efforts to develop new carbon-carbon bond formation methods to transform glycals into other carbohydrate analogues and various useful synthetic building blocks. Palladium catalyzed carbon–carbon bond formation reaction has become a fast growing area of chemistry due to its versatility and chemo selectivity. Palladium catalyzed reactions such as Heck–Mizoroki reaction, Suzuki reaction and Tsuji–Trost reaction have been intensively studied in the past decades. This thesis focuses on applying palladium chemistry to glycals to develop new methodologies on glycal functionalizations. In the first chapter, a new Pd(OAc)2 catalyzed direct alkene-alkene coupling of glycals and other alkenes such as acrylates and styrenes is described. The concept of this methodology is to apply the palladium catalyzed C–H activation on glycal functionalizations. The coupling reaction selectively takes place on C2 of the glycals to form sugar containing dienes. In the second chapter, a Heck type C-glycosylation of glycals and enol triflates is demonstrated. In this reaction, the Nobel winning Heck reaction is applied on glycals to give exclusively C1 regioselectivity and α stereoselectivity. The substrate scope includes glycals from different sugar origins and enol triflates of different sizes. Another Heck type α selective C-glycosylation methodology of glycals and aryl hydrazines towards aryl-C-glycosides is reported in the third chapter. The mechanism of α selectivity is also studied in this chapter. In the last chapter, a dual catalyzed reaction by integrating the renowned palladium catalyzed Tsuji–Trost reaction and NHC catalysis is introduced. The two catalysts exert their effects simultaneously and parallelly to afford the nucleophilic addition product. The concept is first tried on simple allylic system and then on glycals with ethoxycarbonyloxyl protecting group on C3. In both cases, the aldehyde origins of the nucleophilic Breslow intermediate are o-azaarylcarboxaldehydes.